Evaluasi Sistem Informasi Penjualan PT SPNS - Anderes Gui; Sanyoto Gondodiyoto; Japari Japari (ComTech: Computer, Mathematics and Engineering Applications, 2010)
The purpose of this paper is to identify and analyze problems that occur in information systems sales PT SPNS. It also serves to control the management and control of applications running well so it can produce accurate information for decision making. The method used is book study method and field study. Study was done by reading library books, scientific papers and other sources, while the field study was done by observation, interviews, and questionnaires. The result of the evaluation is derived from the respective strengths and weaknesses - each control. Weaknesses are found, the findings presented in the form of a matrix that contains the findings and recommendations as a matter of risk remedial action. Conclusions obtained from the audit for security control, operations, limitations, input and output is good enough because it can satisfy and support the sales activities of PT SPNS.